Book Review: Religion, Conflict, and Peacebuilding the Role of Religious Leadership Bosnia and Herzegovina: A Review Essay - Fithriya, Dwi Nur Laela (Jurnal Sosiologi Reflektif, 2024)
The book Religion, Conflict, and Peacebuilding by Stipe Odak examines the role of religion in conflicts and peacebuilding efforts, focusing on Bosnia and Herzegovina. This book emerges amidst the rise of religiously motivated violence, such as the events of 2014, and addresses a critical question: Can religion be part of the solution when it is often perceived as part of the problem? In terms of substance, Odak explores how religious leaders can either exacerbate or mitigate conflicts and how they serve as agents of change in the peace process. The book is based on interviews with religious leaders and in-depth case studies, discussing strategies for interfaith dialogue and faith-based peace initiatives. Odak highlights two contrasting realities: violence fueled by religious beliefs and the substantial efforts by religious individuals and institutions to foster peace. Criticism of the book centers on its narrow geographic focus, which may lead readers to feel that its findings are confined to the Balkan context. Additionally, the book lacks a deeper critical analysis of the potential biases of religious leaders in their approaches. Nevertheless, it makes a significant contribution to the literature on religion, conflict, and peacebuilding, particularly for those interested in the dynamics of religion-based conflicts. Buku Religion, Conflict, and Peacebuilding karya Stipe Odak mengkaji peran agama dalam konflik dan upaya perdamaian, dengan fokus pada Bosnia dan Herzegovina. Buku ini muncul di tengah meningkatnya kekerasan bermotif agama, seperti yang terjadi pada tahun 2014, dan menyoroti pertanyaan penting: Dapatkah agama menjadi bagian dari solusi ketika sering kali dianggap sebagai penyebab masalah? Secara substansi, Odak mengeksplorasi bagaimana pemimpin agama dapat memperburuk atau mengurangi konflik dan bagaimana mereka berperan sebagai agen perubahan dalam proses perdamaian. Buku ini didasarkan pada wawancara dengan pemimpin agama dan studi kasus yang mendalam, serta membahas strategi dialog antar iman dan inisiatif perdamaian berbasis agama. Odak menunjukkan dua realitas yang bertentangan: kekerasan yang didorong oleh keyakinan agama dan upaya besar dari individu dan lembaga agama dalam membangun perdamaian. Kritik terhadap buku ini berfokus pada pendekatannya yang sempit secara geografis, sehingga pembaca mungkin merasa bahwa temuan buku ini terbatas untuk konteks Balkan saja. Selain itu, analisis kritis terhadap bias yang mungkin dimiliki oleh para pemimpin agama dalam pendekatan mereka belum digali secara mendalam. Meskipun demikian, buku ini memberikan kontribusi yang signifikan dalam literatur tentang agama, konflik, dan resolusi perdamaian, terutama bagi mereka yang tertarik pada dinamika konflik berbasis agama.